The Demand for Feedback and its Value in a Management Accounting Course - Timothy J.; Paul M. Goldwater (Universitas Pendidikan Ganesha, 2022)
Little effort has been expended on studying the role of feedback in accounting education. While most concerned consider that any precise information about students' thinking has value, such beliefs have not been empirical. They are using data generated by computerized databases that offer on-demand solutions to problems in management accounting courses. This research aims to analyze the feedback and its value in the Management Accounting course. The context for this research is an introduction to management accounting courses offered at major public universities in the Southeastern United States during the final semester. Two student sections taught by the same instructor opened 143 students majoring in accounting. The methods used to collect data are quizzes and tests. The technique used to analyze the data is descriptive qualitative and quantitative analysis. The result of this research is that there is a positive relationship between the frequency of access to feedback and higher academic performance. The timing of student access to solutions depends, in a meaningful way, on mastery of the material. The longer a student waits to demand a solution, the worse their performance will be. Important feedback on the effect of effort (H3 and H4) can provide additional or alternative meaning when juxtaposed with the significance of the non-hypothesized relationship between effort and performance.